Level of exoskeleton support influences shoulder elevation, external rotation and forearm pronation during simulated work tasks in females. (January 2022) - McFarland, Tasha C.; McDonald, Alison C.; Whittaker, Rachel L.; Callaghan, Jack P.; Dickerson, Clark R.
Abstract: Despite growing literature, limited research details the influence of passive upper limb exoskeletons on upper limb kinematics. Two bolting tasks and a tracing task were completed at two heights (overhead and between waist and overhead height) for four exoskeleton conditions (no exoskeleton, and 3 levels of exoskeleton assistance) by female participants. Motion capture data, ratings of perceived exertion and discomfort, and task duration were recorded. Exoskeleton condition increased minimum shoulder elevation by 35–36% (Δ10.5–10.7°) at 1.81 kg and 2.72 kg of support, mean shoulder external rotation by 316% (Δ24.6°) at 0.91 kg of support and mean forearm pronation by 30.9% (Δ14.6°) at 0.91 kg of support. Exoskeleton condition reduced ratings of perceived exertion and discomfort, but not significantly. Task duration was unaffected. Exoskeleton use at any of three different settings modestly affected some joint kinematics for the tasks examined, which may merit consideration when deciding on occupational exoskeleton implementation. Highlights: Exoskeleton use increased minimum shoulder elevation by 35–36% (Δ 10.5–10.7°). Exoskeleton use increased mean shoulder external rotation by 316% (Δ 24.6°). Exoskeleton use increased mean forearm pronation by 30.9% (Δ 14.6°). Exoskeleton use reduced perceived discomfort and exertion but not significantly. Exoskeleton use at three settings modestly affected most joint kinematics.